2000
DOI: 10.1002/(sici)1098-1098(2000)11:1<81::aid-ima9>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional digital topological characterization of cancellous bone architecture

Abstract: Cancellous bone consists of a network of bony struts and plates that provide mechanical strength to much of the skeleton at minimum weight. It has been shown that loss in bone mass is accompanied by architectural changes that relate to both scale and topology of the network. In this paper, the concept of three‐dimensional (3D) digital topology is presented for characterizing the local topology of each bone voxel after skeletonization of the binary bone images. This method allows us to identify each voxel as be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 21 publications
(19 reference statements)
0
110
0
Order By: Relevance
“…At least three studies provide compelling evidence for the independent role of architecture as a predictor of bone strength. In 2001 Wehrli et al (169) showed in 79 women, of whom 29 had vertebral fractures, that topological parameters derived by DTA of skeleton networks (141), discussed in earlier sections of this review, were far stronger discriminators of the two groups than BMD. This study provided, for the first time, in vivo evidence for the architectural and mechanistic consequences of postmenopausal bone loss in that fracture subjects had lower surface-to-curve ratio and higher erosion index than their unfractured peers.…”
Section: Clinical Applications Of Trabecular Bone Microstructural Anamentioning
confidence: 87%
See 1 more Smart Citation
“…At least three studies provide compelling evidence for the independent role of architecture as a predictor of bone strength. In 2001 Wehrli et al (169) showed in 79 women, of whom 29 had vertebral fractures, that topological parameters derived by DTA of skeleton networks (141), discussed in earlier sections of this review, were far stronger discriminators of the two groups than BMD. This study provided, for the first time, in vivo evidence for the architectural and mechanistic consequences of postmenopausal bone loss in that fracture subjects had lower surface-to-curve ratio and higher erosion index than their unfractured peers.…”
Section: Clinical Applications Of Trabecular Bone Microstructural Anamentioning
confidence: 87%
“…The method, termed digital topological analysis (DTA) was subsequently refined and applied to digital images of trabecular bone (140,141). DTA relies on the three local topological entities described above, i.e.…”
Section: D Structure Analysismentioning
confidence: 99%
“…5 The EI is defined as the ratio of all topological parameters expected to increase during the erosion process (specifically, curve, curve-edge, surface-edge, profile-edge, and curve-curve-junction types) compared with those that are expected to decrease (surface and surface-surface junction types). 21 …”
Section: Digital Topological Analysismentioning
confidence: 99%
“…A special class of networks is "partially connected networks," in which nodes are connected only to adjacent nodes (neighbors), so that the network is fully connected without the cost of maintaining the maximal possible number of edges. Saha et al (2000) paved the way for studying trabecular bone topology-the manner in which individual elements collectively form a 3D network-by suggesting a method of uncoupling trabecular morphology from the 3D organization of the axes, or centroids, of trabeculae in a sample (edges). The topological approach itself helps explain the mechanical properties and might well determine the 3D architectural blueprint, or archetype, of trabecular bone that has been optimized throughout evolution and allows for further functional adaptation (i.e., local Tb.Th, DA, and bone volume fraction being superimposed on topological parameters such as connectedness and continuity).…”
Section: Introductionmentioning
confidence: 99%